ANALISIS HEAD LOSSES VERTICAL PUMP-A PADA DEWATERING SYSTEM DI POWER HOUSE PLTA KERINCI MERANGIN HIDRO 350 MW - Sulaiman Ali; Movi Wahyu (Ensiklopedia of Journal, 2026)
This study discusses the analysis of major and minor head losses in the dewatering system at the Kerinci Merangin Hydro Power Plant 350 MW Power House, specifically in Vertical Pump-A. The dewatering system functions to remove water from the turbine components during the maintenance process. The calculation uses the Darcy-Weisbach approach for major head losses, and local coefficients for minor head losses. The Reynolds number is also calculated to determine the type of fluid flow. The analysis results show that the major head loss in the DN 400 pipe reaches 4.41 meters and the minor is 0.21 meters, with a total pressure loss of 4.62 meters. These results demonstrate the importance of efficient piping system planning to minimize energy loss.Keywords: head losses, dewatering, vertical pump, piping system, hydropower